Can Variation in Subgroups' Average Treatment Effects Explain Treatment Effect Heterogeneity? Evidence from a Social Experiment - Bitler, Marianne P.; Gelbach, Jonah B.; Hoynes, Hilary W. (The Review of Economics and Statistics, 2017)
We assess whether welfare reform affects earnings only through mean impacts that are constant within but vary across subgroups. This is important because researchers interested in treatment effect heterogeneity typically focus on estimating mean impacts that only vary across subgroups. Using a novel approach to simulating treatment group earnings under the constant mean impacts within subgroup model, we find this model does a poor job of capturing treatment effect heterogeneity for Connecticut's Jobs First welfare reform experiment. Notably, ignoring within-group heterogeneitywould lead one to miss evidence that treatment effects are consistent with basic labor supply theory.